Perbedaan Kemampuan Pemahaman Konsep Matematis Siswa pada Materi Luas Bangun Datar antara Model Pembelajaran Inquiry dengan Explicit Instruction Berbantuan Puzzle - Dalimunthe, Amril; Fauzi, Kms Muhammad Amin; Azis, Tian Abdul (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to analyze the differences in the ability of students to understand mathematical concepts taught by using Inquiry and Explicit Instruction learning models assisted by puzzles on the flat shape material in class V. This research is a quantitative study with a Quasi-experimental method. Determination of research samples using purposive sampling method where the sample is determined based on research objectives. The sample of this study consisted of two classes, namely VA with the Inquiry model and VB with the Explicit Instruction model assisted by puzzle. The research variables consisted of Inquiry and Explicit Instruction learning models as independent variables and learning outcomes as the dependent variable. The results showed that there were differences in the students' initial ability to understand mathematical concepts in the flat shape material in class V. The average pretest scores of students in the Inquiry (VA) class were 24.20 and Explicit Instruction (VB) 26.30. After that, a posttest was carried out to determine the differences in learning outcomes in the two research samples. The results of the posttest showed that the mean value of the VA class taught using the Inquiry model increased to 52.6 and the VB class taught using the explicit instruction model increased to 64.34. The results of the analysis of variance test showed that there was a difference in the average understanding of students' mathematical concepts taught by using Inquiry and Explicit Instruction learning models assisted by puzzles on the area of flat shapes.